Learner-centered approach in the teacing english language (Eurasian Journal of Philology Science and Education, 2016)
Thearticle under consideration deals with the new deductive forms in teaching in contemporary education system, that is about learnercentered approach, which enables to implement the active forms into the teaching process that helpsto develop students’ creative abilities. Particularly the project based learning grounded in the development of students’ cognitive skills is directed to unlock creativity and fresh thinking. This kind of activity is oriented to personal retrieval of new solutions and new information. Self regulated learners are successful because they control their learning environment. They exert this control by directing and regulating their own actions toward their learning goals. Self regulated learning should be used in three different phases of learning. The first phase is during the initial learning, the second phase is when troubleshooting a problem en countered during learning and the third phase is when they are trying toteach others (Palincsar& Brown, 1984).
Keywords: English language; learnercentered approach; cognitive skills is directed to unlock creativity and fresh thinking